2009
DOI: 10.1261/rna.1812710
|View full text |Cite
|
Sign up to set email alerts
|

Massive expansions of Dscam splicing diversity via staggered homologous recombination during arthropod evolution

Abstract: The arthropod Down syndrome cell adhesion molecule (Dscam) gene can generate tens of thousands of protein isoforms via combinatorial splicing of numerous alternative exons encoding immunoglobulin variable domains organized into three clusters referred to as the exon 4, 6, and 9 clusters. Dscam protein diversity is important for nervous system development and immune functions. We have performed extensive phylogenetic analyses of Dscam from 20 arthropods (each containing between 46 and 96 alternative exons) to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 48 publications
8
44
3
Order By: Relevance
“…It contains a cluster of MXEs (exons 3b–3e) that is differentially included into a set of two exons (exon 3 and exon 4), and the two sets are themselves mutually exclusive (Fig 1F, Appendix Figs S16 and S17). The identification of large clusters with multiple MXEs and many genes with multiple clusters shows that complex mutually exclusive splicing is not restricted to arthropods (Schmucker et al , 2000; Graveley, 2005; Lee et al , 2010; Hatje & Kollmar, 2013) but might be present in all bilateria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It contains a cluster of MXEs (exons 3b–3e) that is differentially included into a set of two exons (exon 3 and exon 4), and the two sets are themselves mutually exclusive (Fig 1F, Appendix Figs S16 and S17). The identification of large clusters with multiple MXEs and many genes with multiple clusters shows that complex mutually exclusive splicing is not restricted to arthropods (Schmucker et al , 2000; Graveley, 2005; Lee et al , 2010; Hatje & Kollmar, 2013) but might be present in all bilateria.…”
Section: Resultsmentioning
confidence: 99%
“…Mutually exclusive splicing generates alternative isoforms by retaining only one exon of a cluster of neighbouring internal exons in the mature transcript and is a sophisticated way to modulate protein function (Letunic et al , 2002; Meijers et al , 2007; Pohl et al , 2013; Tress et al , 2017a). The most extreme cases known so far are the arthropod DSCAM genes, for which up to 99 mutually exclusive exons (MXEs) spread into four clusters were identified (Schmucker et al , 2000; Lee et al , 2010; Pillmann et al , 2011). …”
Section: Introductionmentioning
confidence: 99%
“…The majority of invertebrate tandem exon duplications associated with mutually exclusive splicing resulted from homologous recombination (HR) events that engaged the upstream intron in each case (73). A HR-mediated duplication of the U2AF1 intron 2–exon 3 segment (Figure 5A) would also explain the mutually exclusive splicing of exons Ab and 3 as well as the existence of the two regions of vertebrate conservation, which are located at a similar distance from their 3′ss (Figure 3A) and share significant sequence identity (Supplementary Figure S8).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, even though most L. vannamei genes (including Dscam) show a high homology to the corresponding P. monodon gene, the expression of more highly diverse PmDscam alternative sequences in P. monodon might still be due to species difference. A comparison of 20 arthropod Dscam genomic sequences found that the number of alternative exons within many exon clusters varied significantly [17]. For instance, in the exon cluster encoding N-terminal Ig3 domain, the number of alternative sequences ranges from 22 to 52.…”
Section: Discussionmentioning
confidence: 99%